6 Monopole Elements Array Intelligent Antennas for IoT Based Environmental Surveillance Network - Elyas Palantei; Arif Hidayat; Wardi Wardi; Intan Sari Areni; Sunarno Sunarno; Eko Setijadi; Dewiani Jamaluddin; Merna Baharuddin; Ahmad Khatami; Muhammad Sabirin Hadis; Akbar Hendra; Nurfitri Kaharuddin; Priska Wina; Mainsuri Mainsuri; Vickyarnoldo Wantura; Mulyadi Mulyadi (EPI International Journal of Engineering, 2020)
Three types of 6 monopoles array intelligent antennas was numerically and practically examined. The main purposes of the investigation is to guarantee that those designed antennas are feasible to implement and to install in a particular IoT based environmental surveillance network configuration. The basic differences of the three intelligent antennas lied on the frequency operations (i.e. 433 MHz, 875-915 MHz and 2.5 GHz) and the actual environment operations (whether for indoor or outdoor). The extreme differences of such frequency operations, of course, affecting the differences on the whole antenna physical dimension. The higher the frequency operation determined then the smaller the physical size of the designed antennas produced. However, the deep intelligent antenna evaluations presented in the paper is the one that operated on frequency band of 875 -915 MHz. The intelligent electronic part of six monopole wire elements arrayed on a circular ground plate was composed of LoRa chip module, Android Uno microcontroller, and the switching network part. The three parts determined whole antenna operation throughout the IoT network. The results of whole antenna examinations are thoroughly discussed in the paper.